Expression and Function of the Cholinergic System in Immune Cells - Fujii, Takeshi; Mashimo, Masato; Moriwaki, Yasuhiro; Misawa, Hidemi; Ono, Shiro; Horiguchi, Kazuhide; Kawashima, Koichiro (Frontiers in Immunology, 2017)
T and B cells express most cholinergic system components – e.g. acetylcholine (ACh), choline acetyltransferase (ChAT), acetylcholinesterase and both muscarinic and nicotinic ACh receptors (mAChRs and nAChRs, respectively). Using ChATBAC-eGFP transgenic mice, ChAT expression has been confirmed in T and B cells, dendritic cells and macrophages. Moreover, T cell activation via TCR/CD3-mediated pathways up-regulates ChAT mRNA expression and ACh synthesis, suggesting this lymphocytic cholinergic system contributes to the regulation of immune function. Immune cells express all five mAChRs (M1-M5). Combined M1/M5 mAChR-deficient (M1/M5-KO) mice produce less antigen-specific antibody than wild-type (WT) mice. Furthermore, spleen cells in M1/M5-KO mice produce less TNF-alpha and IL-6, suggesting M1/M5 mAChRs are involved in regulating pro-inflammatory cytokine and antibody production. Immune cells also frequently express the alpha2, alpha5, alpha6, alpha7, alpha9 and alpha10 nAChR subunits. Alpha7 nAChR-deficient (alpha7-KO) mice produce more antigen-specific antibody than WT mice, and spleen cells from alpha7-KO mice produce more TNF-alpha and IL-6 than WT cells. This suggests alpha7 nAChRs are involved in regulating cytokine production and thus modulate antibody production. Evidence also indicates that nicotine modulates immune responses by altering cytokine production, and that alpha7 nAChR signaling contributes to immunomodulation through modification of T cell differentiation. Together, these findings suggest the involvement of both mAChRs and nAChRs in the regulation of immune function. The observation that vagus nerve stimulation protects mice from lethal endotoxin shock led to the notion of a cholinergic anti-inflammatory reflex pathway, and the spleen is an essential component of this anti-inflammatory reflex. Because the spleen lacks direct vagus innervation, it has been postulated that ACh synthesized by a subset of CD4+ T cells relays vagal nerve signals to alpha7 nAChRs on splenic macrophages, which down-regulates TNF-alpha synthesis and release, thereby modulating inflammatory responses. However, because the spleen is innervated solely by the noradrenergic splenic nerve, confirmation of an anti-inflammatory reflex pathway involving the spleen requires several more hypotheses to be addressed. We will review and discuss these issues in the context of the cholinergic system in immune cells.